FIFO Method Improvement and Adjustment Design for PT. ABC Warehouse Plans - Handayani, Melia; Maulani, Syifa Fajar; Nirmala, Ira; Ardani, Maskur Faris; Ageng, Brilliant Hanief; Firmansyah, Ridho; Rammadhani, Faishal Sauqi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Face film company PT. ABC requires an efficient and organized storage system to secure raw materials and finished products. However, warehouses currently experience problems with random storage, which causes human error, overstocking, and potential product damage. This research aims to design layout improvements and adjustments to the FIFO (First in First Out) method in PT A B C's warehouse plan. The research method used is qualitative with observation, interviews and literature study. Observation results show discrepancies in warehouse layout that disrupt operational flow, as well as the need for restructuring and improving the management system. Through design improvements, such as rearranging the layout, more strategic placement of goods, and implementing the FIFO method, it is hoped that it can increase warehouse operational efficiency, reduce the risk of goods damage, and speed up the delivery flow to customers. More comprehensive improvements, including inventory management and staff training, are also needed to ensure the successful implementation of an effective FIFO system. Thus, this research contributes to improving warehouse management and operational efficiency of PT. ABC.